WATERSKETCH: TOWARDS SUSTAINABLE RIVER BASIN MANAGEMENT IN THE BALTIC SEA REGION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
River basin planning in the Baltic Sea Region (BSR) has always been a complex, yet important topic, which has gained a new momentum with the approval of EU Water Framework Directive (WFD) in December 2000. The ultimate goal of WFD is to achieve a good ecological status/potential of all water bodies before 2015. Together with the implementation of WFD also principles of Integrated Coastal Zone Management (ICZM) are to be applied and national expansions of Natura 2000 networks are in progress.There are many elements which are important in river basin planning systems. In the Baltic Sea region for example, the pressures posed by economic activities including increasing tourism and port activities have to be considered in land and river basin planning. These matters are dealt with in the context of the Watersketch project, a scheme supported by the Interreg IIIB programme of the European Union. The project aims at producing an extensive planning system and a working scheme that accounts for the various, complex and opposing tasks currently subjected to water usage. The main goal is to produce and describe processes, that aid planning and decision making also in areas with limited resources to meet the diverse requirements concerning water. In addition, the project intends to:1) analyse and synthesize the different directives and conventions focused on use of water courses.2) demonstrate the major alternatives of river basin planning with a wide set of case studies ranging from southern tip of Baltic Sea (Poland) to northernmost corner of it (Norway).3) provide a Water Planning Decision Support System for spatial planners, which takes into account all main components needed for economically, socially and ecologically sustainable use of water courses.Raise capacity to promote the sustainable development in river basins by means of an information exchange platform, training workshops and the dissemination of the information needed for sustainable use of river basins by means of a handbook.By a combined approach where planning is complemented by training and information exchange, this project will provide a long-term contribution towards addressing the problem, at the same time that it links itself with other similar projects, achieving synergy and avoiding duplications.